Effect of different nanoscale microelements containing formulations for seed treatment on germination and growth of maize seedlings - Nguyen Hoai Chau,; Chu Thi Hao,; Doan Quang Ha,; Dao Trong Hien,; Le Thi Phuong,; Nguyen Thi Thuy,; Ngo Quoc Buu, (Vietnam Journal of Science and Technology, 2018)
Effect of the nutrient formulations for pre-sowing seed treatment on germination and growth of maize seedlings was studied. The formulations comprised separate copper nanoparticles (NanoCu), IET1- based on a Novalon Seed Treatment product, IET2 - based on humate metal-organic-coordination complexes (MOC), Nualgi – based on nano silica, wherein microelements were adsorbed on the surface of the silica nanoparticles, and formulations with microelements in a form of Metal-EDTA complexes, based on commercial fertilizer products of Novalon, Wuxal and Comex companies. Results of the study showed that all the tested formulations, except for the separate nanocopper formulation, demonstrated visibly higher stimulation effects on the maize seedlings growth, among which the nanoscale microelements-containing seeds treatment formulations produced in Institute of Environmental Technology (IET1 and IET2) exhibited the best growth indices although non-significantly differed as compared with the control. The experimental data presented also proved that for obtaining stable stimulation effects on the plant growth kinetics instead of using separate nanosized microelement it is preferable to use complex formulations, wherein besides of microelements there are other components included such as plant regulators, amino- and carboxylic acids, plant protection agents etc.